Zusammensetzung und Dichte der Harnstoffschmelze und der koexistierenden Gasphase - W. Durisch; A. Buck (CHIMIA)
An experimental method for the determination of the composition and density of the coexisting phases in the vapour-liquid carbon dioxide/ammonia/water equilibrium system at high pressure and temperature is presented. Apart from the elemental analysis of the vapour phase, which required a specially developed sampling procedure, the chemical analyses were carried out by ordinary analytical methods. For the measurement of the vapour phase density, a high pressure high temperature gas pycnometer from a high alloy stainless steel was used. Results, including the concentration of urea in the vapour phase and of ammonium carbamate in the liquid phase are given for a charge density of 0.53 g/cm3, at a temperature of 170 °C, and initial NH3:CO2 and H2O:CO2 molar ratios of 2 and 0, resp.